Spin of a batted ball toward the opposite field in baseball - Nakashima, H. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to investigate the spinning motion of a ball batted toward the opposite field in baseball. A pitching machine was used to launch the balls toward the bat, which was adjusted and tied up to hit the balls in the opposite field. The ball movements were recorded using three high-speed video cameras. The results indicated that the batted ball backspin and sidespin components correlate strongly with the launch elevation angles and launch horizontal angles, respectively. All the batted balls had a certain amount of sidespin components. The balls batted toward the opposite field experienced unavoidable horizontal Magnus force, resulting in curving. Thus, it is important to launch the balls with a larger velocity to hit a long ball toward the opposite field while comparing with the balls batted towards the same field with less sidespin components.